Active Design of Contact Pattern and Experimental Verification of the Aero Spiral Bevel Gear - Qian Lulu; Liu Hai'ou; Gao Jian; Lou Peng (Jixie chuandong)
In this study, an aero spiral bevel gear box is taken as the research object. An active design method for the bevel gear contact pattern is proposed. Firstly, the tooth surface design is carried out based on the macro parameters of spiral bevel gears and GEMS software, and then the accurate tooth surface of the gear pair is obtained. Secondly, after considering the influence of the transmission system deformation under load and bearing clearance and machining error and so on, the system-level contact pattern analysis model for spiral bevel gears is established, and the contact pattern and the vibration response under the working condition are obtained. Thirdly,applying the above design tooth surface to machining, designing the experiment, and comparing the contact pattern and the vibration response obtained from the simulation and the experiment, the reliability of the simulation analysis model is verified. Finally, based on the simulation analysis model, the contact pattern optimization of the above tooth surface is done, the tooth surface meeting the requirements of strength and vibration performance is obtained, and the active design method of spiral bevel gear contact pattern is formed.